(untitled) (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2018)
This article resumes a ethnographic research has been carried out among Latino American migrant musicians at Andalucia (Spain). We will study the process of migration and their musician abilities as survival strategies. Gender perspective helps us to study inequalities between women and men at different music works, especially on stereotypes that are present at migration process and their incorporation to work world. Feminist Ethnography allowed us to analyze emotions in front of migration memories both women and men musicians. So we consider this aesthetic emotion was significant in our ethnography work, because it is a very important emotion in the musical performs. Empathy was the main ethnographic activity in front of memories of these persons, both artists and migrants.